Food safety training influence on food service workers’ knowledge and compliance to Malaysia Food Hygiene Regulations 2009 - Johnson, O.; W.-Z.-S., Wan-Hafiz; Mahyudin, N.A.; Jaafar, S.N. (Rynnye Lyan Resources, 2023)
This study was conducted to evaluate the influence of food safety training on the knowledge and compliance of food service workers with Malaysia Food Hygiene Regulations 2009 in Cyberjaya, Selangor, Malaysia. Data were collected from 261 food service workers (108 casual dining restaurant owners and 153 food handlers) through a survey by means of a questionnaire which consisted of questions on business and premises profiles, history of premises inspection and knowledge of food hygiene aspects as outlined in the Malaysia Food Hygiene Regulations 2009. The results showed that there was a significant positive association (p<0.05) between attending food safety training and the level of respondents’ knowledge of Malaysia Food Hygiene Regulations 2009. There was a significant positive association (p<0.05) between respondents’ knowledge and the level of compliance with Malaysia Food Hygiene Regulations 2009 with different food safety training providers. There was also a significant positive association (p<0.05) between respondents’ knowledge and the level of compliance with Malaysia Food Hygiene Regulations 2009 with food safety training sources. In conclusion, over half of the food service workers showed satisfactory food safety knowledge and compliance with Malaysia Food Hygiene Regulations 2009. This study found that there was a significant relationship (p<0.05) between food service workers’ knowledge and compliance with Malaysia Food Hygiene Regulations 2009. A significant relationship (p<0.05) was also found in knowledge and level of compliance with all food safety training factors (food safety training attendance, food safety training providers and food safety training sources) in the Malaysia Food Hygiene Regulations 2009. Hence, hypotheses H1, H2 (H2a, H2b, H2c) were accepted. It is suggested that in related future research, data are collected from a larger sample size and at different locations to gain more comprehensive outcomes.